CHIP: Community Historical Interest Projects - Joe Rivers (Middle Grades Review, 2019)
This practitioner perspective presents a process in which state-wide initiatives can be used as tools for creating place-based, project-based collaborations between students and local organizations within the community. Vermont is focusing on Content Proficiencies, Transferable Skills, Flexible Pathways and Multi-Tiered Systems of Support. CHIP is an effort to combine these initiatives and offer students meaningful school work that provides a real service for, and connects students with, the local community.
Keywords: Middle school; middle level education; early adolescence; place-based education; community-based education